Selection of Surrogates For Drought Resilience In Temperate Maize (Zea Mays L.) (Bangladesh Journal of Botany, 2022)
Drought is one of the major constraints affecting the economic yield of maize worldwide. Present study was carried out to select the surrogates for drought resilience in 70 maize landraces collected from diverse agro-ecologies of Kashmir Himalayas. Significant variation was observed among the genotypes for all the traits under well-watered and drought conditions. Due to the drought stress, the highest reduction was observed for the canopy temperature (175.18%), followed by root volume (69.77%), top root biomass (69.1%), shoot biomass (67.2%), bottom root biomass (53.75%), chlorophyll content (22.85 SPAD units) and shoot height (21.63%). The reduction was also recorded for other traits like shoot to total biomass ratio (2.70%), relative water content (13.42 %), cell membrane stability (17.33%) and rooting depth (19.86%). Root to total biomass ratio was found to increase in response to drought stress (7.69%). A positive significant correlation was observed between grain yield and root volume, top root biomass, bottom root biomass, rooting depth, root to total biomass, chlorophyll content, cell membrane stability, canopy temperature depression and relative water content. These can be used for selection of appropriate surrogates of drought tolerant genotypes. The landraces viz., KD-L35, KD-L37, KD-L19, KD-L23, KD-L17, KD-L21, KD-L46, KD-L43, KD-L29, KD-L25 and KD-L38 showed promising performance under drought for most of the surrogates identified. The landraces selected can be used as sources of novel and/or favourable alleles to breed for climate resilient maize cultivars.Bangladesh J. Bot. 51(3): 487-498, 2022 (September)